EMANCIPATORY ROOTS OF EDUCATION - Araujo, Geisiane dos Santos; Rosa, Paulo Roberto [UNESP]; Felicio, Munir Jorge [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
As a specifically human activity, education contributes to maintain or to modify the conception of the world, life, and human being. To debate the emancipatory roots of education, this text gathered the contributions of Brandao (1991), Freire (2009) and Caldart (2004) as means to deepen our understanding of the three different conceptions of education. The first concept conceives education as a knowledge exchange network, which neither depends nor is attached to any model of formal teaching. The second shows that the sole and most fundamental goal of education consists of an act of courage to discuss life, where it is thought that human being remains in a constant movement in search for oneself. Finally, it is conceived as the process of new social formation that seeks to build a strategy that will break the control and dominance of the capital. It is concluded that education is an unfinished task and it involves every dimension of the human being in the perspective of emancipation.
Keywords: Education; Emancipation; Human being; Participation